Competition and Succession in Pastures 2001
DOI: 10.1079/9780851994413.0261
|View full text |Cite
|
Sign up to set email alerts
|

Competition and succession in re-created botanically diverse grassland communities.

Abstract: Recreational values Amenity values Feed production Botanically diverse grassland communities Invertebrates Vertebrates Fig. 13.1. Schematic representation of the agricultural and environmental values of botanically diverse grassland communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Research into the effectiveness of AES has shown that the restoration of floristically species-rich, semi-natural habitats in grasslands previously used intensively for agricultural purposes is frequently difficult to achieve simply by a reduction in the intensity of cultivation (Berendse et al 1992;Chapman 2001;Herzog et al 2005;Kleijn et al 2004;Kleijn and Sutherland 2003;Pywell et al 2007). Poor soil seed banks (Bekker et al 1997), high nutrient levels in the soil, especially phosphorus and nitrogen (Bakker and Berendse 1999;Critchley et al 2002;Gough and Marrs 1990;Janssens et al 1998;McCrea et al 2004;Mountford et al 1993), limited capacity for the seeds to disperse (Mortimer et al 1998), a lack of desired species in the surrounding area (Poschlod et al 1998;Schmidt 2007), and a lack of a residual pool of target species in extensively used grasslands (Klimkowska et al 2007;Rosenthal 2006) are the main factors hindering grassland restoration.…”
Section: Introductionmentioning
confidence: 98%
“…Research into the effectiveness of AES has shown that the restoration of floristically species-rich, semi-natural habitats in grasslands previously used intensively for agricultural purposes is frequently difficult to achieve simply by a reduction in the intensity of cultivation (Berendse et al 1992;Chapman 2001;Herzog et al 2005;Kleijn et al 2004;Kleijn and Sutherland 2003;Pywell et al 2007). Poor soil seed banks (Bekker et al 1997), high nutrient levels in the soil, especially phosphorus and nitrogen (Bakker and Berendse 1999;Critchley et al 2002;Gough and Marrs 1990;Janssens et al 1998;McCrea et al 2004;Mountford et al 1993), limited capacity for the seeds to disperse (Mortimer et al 1998), a lack of desired species in the surrounding area (Poschlod et al 1998;Schmidt 2007), and a lack of a residual pool of target species in extensively used grasslands (Klimkowska et al 2007;Rosenthal 2006) are the main factors hindering grassland restoration.…”
Section: Introductionmentioning
confidence: 98%
“…Changes in soil fertility as a result of cropping may influence the composition of the postcropping plant community (Grime 1979). Higher levels of fertility, as might be promoted by crop fertilisation, have been shown by several studies to favour fast-growing competitive species (Chapman 2001), reduce species diversity (McCrea et al 2004) or favour annuals over perennial grasses (Bolger and Garden 2002;Prober et al 2005;Hacker et al 2008). The development of 'islands of fertility' under shrub canopies (Schlesinger et al 1990(Schlesinger et al , 1996Døckersmith et al 1999) due to litter fall, soil accretion, and animal and fecal decomposition (Rhoades 1996) could result in nutrient distribution patterns which if persistent might favour re-establishment of trees or shrubs (Døckersmith et al 1999) over native perennial grasses.…”
Section: Introductionmentioning
confidence: 99%